THE RECONSTRUCTION OF “JEPIN TALI” SINTANG DANCE - Sari, Anggi Wulan; Widyastituningrum, Sri Rochana (ARTISTIC : International Journal of Creation and Innovation, 2022)
Jepin Tali dance is one of the traditional Malay dances from Sintang Regency, West Kalimantan Province. This Jepin Tali dance was very popular then, especially among the Malay tribe community, because the community participated in dancing or bejepen at every performance. This is a group dance performed by both male and female dancers. However, this dance has been hibernating. Accordingly, this research aims to reconstruct the Jepin Tali dance so it can be revived in the community. This study is a practice-led research. Data were collected through interviews, observation, and literature study. Burra Charter's theory was used in the dance reconstruction. The results of this study indicate that the reconstruction increased the range of motion from 3 to 16 varieties, musical instruments, make-up and clothing, and floor patterns. The dance structure was developed into three parts: the beginning, the core, and the closing, by using the property of eight ropes braided in red, green, blue, and yellow colors and accompanied by music featuring Siti Zubaidah's poetry.